Translating claims‐based CHA2DS2‐VaSc and HAS‐BLED to ICD‐10‐CM: Impacts of mapping strategies. Issue 4 (17th February 2020) - Webster‐Clark, Michael; Huang, Ting‐Ying; Hou, Laura; Toh, Sengwee
Abstract: Purpose: The CHA2 DS2 ‐VaSc and HAS‐BLED risk scores are commonly used in the studies of oral anticoagulants (OACs). The best ways to map these scores to the International Classification of Diseases, 10th Revision, Clinical Modification (ICD‐10‐CM) codes is unclear, as is how they perform in various types of OAC users. We aimed to assess the distributions of CHA2 DS2 ‐VaSc and HAS‐BLED scores and C‐statistics for outcome prediction in the ICD‐10‐CM era using different mapping strategies. Methods: We compared the distributions of CHA2 DS2 ‐VaSc and HAS‐BLED scores from various mapping strategies in atrial fibrillation patients before, during, and after ICD‐10‐CM transition. We estimated the C‐statistics predicting the 90‐day risk of hospitalized stroke (for CHA2 DS2 ‐VaSc) or hospitalized bleeding (for HAS‐BLED) in patients identified at least 6 months after the ICD‐10‐CM transition, overall and by anticoagulant type. Results: Forward‐backward mapping produced higher CHA2 DS2 ‐VaSc and HAS‐BLED scores in the ICD‐10‐CM era compared to the ICD‐9‐CM era: the mean difference was 0.074 (95% confidence interval 0.064‐0.085) for CHA2 DS2 ‐VaSc and 0.055 (0.048‐0.062) for HAS‐BLED. Both scores had higher C‐statistics in patients taking no OACs (0.697 [0.677‐0.717] for CHA2 DS2 ‐VaSc; 0.719 [0.702‐0.737] for HAS‐BLED) or direct OACs (0.695 [0.654‐0.735] for CHA2 DS2 ‐VaSc; 0.700 [0.673‐0.728] for HAS‐BLED) than those taking warfarin (0.655 [0.613‐0.697] for CHA2 DS2 ‐VaSc; 0.663 [0.6320.695] for HAS‐BLED). Conclusions: Existing mapping strategies generally preserved the distributions of CHA2 DS2 ‐VaSc and HAS‐BLED scores after ICD‐10‐CM transition. Both scores performed better in patients on no OACs or direct OACs than patients on warfarin.